Thermally-stable single-atom catalysts and beyond: A perspective - Liu, Sixu; Li, Jiwei; Xiong, Haifeng (Frontiers in Chemistry, 2022)
Single-atom catalysis is a research frontier and has attracted extensive interests in catalysis. Significant progresses have been carried out in the synthesis and characterization of metal single-atom catalysts (SACs). However, the stability and catalytic reactivity of metal SAC at elevated temperatures are not well documented because single atoms sinter at elevated temperatures. Therefore, the development of stable and reactive SAC at high temperatures remains a formidable challenge. In this perspective, we summarize recent efforts on the preparation of the thermally-stable SACs synthesized at elevated temperature via the reverse-Ostwald ripening mechanism, including the approaches of atom trapping and vapor-phase self-assembly. The reducibility of lattice oxygen, the loading upper limit and the location of the metal single atom are discussed, combining experiments with simulations. In addition, we demonstrate that the coordination structure of the metal single atom can be tailored to address the relationship of structure and performances of the metal SAC in reactions. We expect that this perspective can provide some insights to guide the study for the rational design of thermally-stable and active single atom catalysts, which are especially suitable for high-temperature reactions.